A company's organs and its officers as its agents in company contracts / Shanti Thuraisingam - Shanty , Thuraisingham (1998)
This dissertation proposes to examine the organs of the Company and its officers as its agents in company contracts. It will also examine the law in England and Australia pertaining to the said subject and recommend whether Malaysia should be prompted to adopt the statutory reforms of these countries. It is generally said that the human agency through which the capacity of the company can operate or manage and conduct itself lies either in the shareholders acting together in general meeting or the board of directors, the two principal organs of the company. Both these organs have an organic quality of their own and in theory they can exercise all the powers of the This dissertation will firstly look into the various powers of this organs, the source of their company under its memorandum or articles and those conferred to it by statute. However, there is a legal as well as a commercial necessity to divide the powers of the company between these two organs.